Why LINQ Matters: Cloud Composability Guaranteed. (Communications of the ACM, 2012)
The article focuses on the use of the Microsoft .NET Framework component Language-integrated Query (LINQ) to demonstrate composability in component design. It states that LINQ is designed specifically to be composable and is a specification of higher-order operators. It talks about lifting composability from computer programs into cloud computing via representational state transfer, resource specifications in uniform resource identifiers, and mapping between expressions in programs. It suggests that injecting subexpressions closer to data-production sites allows for increased bandwidth and security benefits in Web services using representational state transfer.